The Aftermath Of COVID-19 on Grade 9 and 12 Biology Classes in Lebanon - El Ahmadieh, Abeer (2024)
The purpose of this thesis was to explore the aftermath of COVID-19 in Grade 9 and 12 Biology Classes in Lebanon. The focus of the study was on comparing the content and skills covered in grade 9 and 12 biology curriculums and official exam levels before and after COVID-19 in addition to the teacher's perspective about the impact of online teaching on the learning process of the student’s experience and finding strategies to identify and fill the gaps. Learning loss, as defined by Fuchs et al. (2023), is a decline in expected rates of academic progress. This study adopted a qualitative approach to explore the percentage of lessons lost, changes in the official exam level, and teachers’ perspectives to find strategies to identify and fill the learning gaps identified. The study observed the curriculum and checked the questions of the tests three years before and three years after COVID-19. Three grade 9 and three grade 12 biology teachers participated in the study depending on professional, experienced teachers who worked in three well-known private schools. Qualitative thematic analysis was done depending on the data collected from the semi-structured interviews. To increase the reliability of the thesis results, three sources’ data were triangulated and compared. Findings revealed that online teaching had a huge impact on the presence of the learning experience of the students. Grade 9 students lost covering half the materials usually required, although the level of the questions shows slightly lower level than the ones before COVID-19. While grade 12 students in addition to the loss of about half the materials covered, the level of the questions highly dropped after covid-19. Six themes emerged from interviews with grades 9 and 12 teachers: “Experience and Adaptation to Online Teaching”, “Disruption in curriculum delivery," “Impact on critical thinking and practical skills", “Identification of Learning Gaps and Assessment Strategies”, “Efficacy of Remedial Strategies”, “National Exam Adjustments and Consequences". New questions for future research were raised, and recommendations for biology teachers, stakeholders, and the Ministry of Education were provided.